2017
DOI: 10.1111/bph.13840
|View full text |Cite
|
Sign up to set email alerts
|

Predictive mechanisms linking brain opioids to chronic pain vulnerability and resilience

Abstract: This article is part of a themed section on Emerging Areas of Opioid Pharmacology. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v175.14/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 131 publications
1
12
0
Order By: Relevance
“…Chronic pain is associated with changes in brain structure and function (17)(18)(19) and increased activity in brain regions involved in emotional processing of pain (20).…”
Section: A Target Of Considerable Interest For the Development Of Novmentioning
confidence: 99%
“…Chronic pain is associated with changes in brain structure and function (17)(18)(19) and increased activity in brain regions involved in emotional processing of pain (20).…”
Section: A Target Of Considerable Interest For the Development Of Novmentioning
confidence: 99%
“…Despite the indisputable evidence regarding the contribution of the opioid system to pain modulation, some studies have also suggested that the activity of opioid receptors is more associated with the learning prediction over time rather than the painful outcome [ 54 ]. Moreover, the role of the opioid system in inhibition of fear acquisition has been previously reported by one study that showed the administration of the MOR antagonist naloxone in healthy subjects increases fear acquisition and changes activation profile in the amygdala [ 52 ].…”
Section: Changes In the Endogenous Modulatory Systems Functioning mentioning
confidence: 99%
“…Bidirectional modulation of the ventral striatum is important to reduce or increase nociception, which depends on opioidergic connections from the ACC. Remarkably, it has also been reported that the connectivity between ventral striatum and PFC predicts the prognosis of chronic pain [ 59 ], and (4) all cortical inputs converge to the PAG-RVM-spinal cord, which facilitates or inhibits nociception [ 46 , 54 ]. However, there are still many questions that must be addressed regarding the mechanisms of opioid-induced analgesia, especially in patients with chronic pain syndromes, which have started to be exposed in the last 20 years.…”
Section: Changes In the Endogenous Modulatory Systems Functioning mentioning
confidence: 99%
“…Pain expectations can be experimentally manipulated through administration of a sham analgesic using a number experimental placebo procedures (Morton, Brown, Watson, El-Deredy, & Jones, 2010b; Wager, 2004; Watson et al, 2009a) or by eliciting cue-evoked expectations and testing the resultant pain report (Atlas, Bolger, Lindquist, & Wager, 2010; Brown, Seymour, Boyle, El-Deredy, & Jones, 2008a). The modulation of pain by expectation has received a significant amount of attention, which is reflected in recent meta-analyses and reviews (Amanzio, Benedetti, Porro, Palermo, & Cauda, 2013; Atlas & Wager, 2012; Brown et al, 2011; Finniss, Kaptchuk, Miller, & Benedetti, 2010; Jones & Brown, 2017; Petersen et al, 2014; Price, Finniss, & Benedetti, 2008). Expectations also change pain-related neural activity (Wager et al, 2004).…”
Section: Introductionmentioning
confidence: 99%